P199 Huddling for safety: the first Irish paediatric SAFE collaborative. (June 2019) - MacDonell, Rachel; Fitzsimons, John; Lachman, Peter; Nicholson, Alf
Abstract : Situation Awareness for Everyone (SAFE) is a collaborative programme developed by the Royal College of Paediatrics and Child Health UK to support clinical teams to improve communication, build a safety based culture and deliver better outcomes for children and young people. The programme includes Quality Improvement (QI) theory, situation awareness methodology and planning of safety huddles on the wards. It has been implemented in over 50 teams across the UK and the Quality Improvement Department of the Royal College of Physicians of Ireland are delighted to bring this initiative to Ireland. A National Paediatric Early Warning System (PEWS) was endorsed by the Irish Minister for Health in December 2015. The supporting National Clinical Guideline recommends that hospitals ' support additional safety practices that enhance the PEWS and lead to greater situation awareness among clinicians and multidisciplinary teams, such as incorporating briefings, safety pause and huddles into practice '. Programmes such as SAFE that use quality improvement methods and patient safety science were specified as appropriate to assist hospitals to collaborate in addressing these challenges. 11 consultant-led teams from across Ireland are participating in this SAFE Collaborative. Teams consist mostly of frontline paediatric clinical care providers (Consultants in Paediatric Medicine, Paediatric Nurses, Pharmacists, Dieticians, Hospital Senior Management and Non-Consultant Hospital Doctors). At a series of face-to-face sessions, teams receive mentoring in QI methodology by RCPI QI Faculty, through the IHI Breakthrough Series Collaborative Model, to develop local SAFE improvement projects impacting on Reducing avoidable error and harm to acutely unwell children Improving communication between all individuals involved in a child's care Improving working culture for healthcare staff providing care to children Increasing involvement of parents, children and young people in their care. The teaching faculty includes active patient representation through parent involvement. Participating teams are encouraged to engage with children, parents and carers to guide their improvement efforts. Teams collect a concise monthly dataset to facilitate aggregate and comparative measures on paediatric clinical outcomes. Teams are encouraged to use this data, and to collect other necessary data to inform the outcome, process and balancing measures pertinent to the areas upon which they are focusing their improvement efforts. The National SAFE Improvement Collaborative is in its early stages. However, at this point, experience with similar national collaborative projects indicates that QI methodology will be used effectively to generate improvements to positively impact paediatric patient safety outcomes, through site specific changes.